SAT0479 Increased carotid intima-media thickness can discriminate significant coronary artery stenosis by coronary ct angiogram in patients with psoriatic arthritis. (15th June 2017) - Cheng, TH; Shang, Q; Li, EKM; Wong, KT; Lee, APW; Szeto, CC; Tam, LS
Abstract : Background: PsA patients have increased morbidity & mortality due to cardiovascular disease (CVD). However, their CV risk were underestimated by various CV risk score 1 . Subclinical carotid atherosclerosis may be considered as surrogate marker of coronary artery disease (CAD) in the general population 2 while it remained uncertain for PsA patients Objectives: To assess the relationship between carotid artery disease by ultrasound (US) and CAD by coronary computed tomography angiography (CCTA) and identify US parameters predictive of significant CAD Methods: 91subjects (56 males; age: 50±11 years; disease duration 9.4±9.2 years) without overt CVD who underwent CCTA & carotid US (interval between two exams:2 [1–7] months) were recruited. Carotid intima-media thickness (cIMT)& the presence of plaque were determined by high resolution US in the distal CCA, bulb & proximal ICA bilaterally. Significant coronary artery stenosis was defined as stenosis of the lumen >50% Results: Carotid plaque was present in 33 (36%) patients & coronary plaque was present in 55 (60%) patients while 9 (10%) patients had significant coronary artery stenosis. 36 (40%) patients had non-zero calcium score (CAC+ group).The mean cIMT was significantly higher in CAC+ group compared to CAC=0 group [0.70±0.11mm vs0.64±0.11mm, p =0.031]. There was a trend suggesting the mean cIMT increases with increasing CAC score, while the prevalence of carotid plaque increased significantly with rising calcium score (Table1). The mean cIMT increased significantly with number of coronary vessels habouring plaque, while there was a trend suggesting the max cIMT and the prevalence of carotid plaque may increase in patients with rising number of coronary vessels harboring plaques The mean & max cIMT were significantly higher in SS+ group than SS- group [mean cIMT: 0.76±0.07mm vs0.65±0.12mm, p =0.011; max cIMT: 0.93±0.14mm vs 0.80±0.16mm, p =0.020] (Table1 ). The prevalence of carotid plaque was similar between SS+ & SS- group [29 (35.4%) vs 4 (44.4%), p =0.421]. Using multivariate logistic regression, mean & max cIMT were independent explanatory variable of significant coronary stenosis after adjusting age, gender, disease duration & damaged joint count. The OR of significant coronary stenosis of every 0.01mm increase in mean & max cIMT were 1.07 (95% CI: 1.00–1.15, p =0.042) and 1.06 (95% CI: 1.00–1.11, p =0.036). Mean cIMT of 0.66mm was the optimal cut off for discriminating patients with significant coronary stenosis (sensitivity: 100%; specificity: 44%). ROC analyses demonstrated that mean cIMT (AUC=0.801, p =0.003)has higher power than Framingham CVD risk score (FRS) (AUC=0.756, p =0.012) Conclusions: Increased cIMT is associated with the presence & severity of coronary calcification & obstructive coronary disease on CCTA in PsA patients. cIMT measurement can discriminate PsA patient with significant coronary stenosis better than FRS. PsA patients with moderate CVD risk should have carotid US for better CV risk stratification References: LamHM, ShenJ., et al., Framingham Risk Score Discriminates Coronary Atherosclerosis in PsA Patient Better Than Other Cardiovascular Scores Do [abstract]. Arthritis Rheumatol. 2016;68. Cohen, G.I., et al., Relationship between carotid disease on ultrasound and coronary disease on CT angiography. JACC Cardiovasc Imaging, 2013.6(11). Disclosure of Interest: None declared